Pembiayaan Hijau sebagai Moderator: Literasi Keuangan dan Kebijakan Pemerintah dalam Keberlanjutan UMKM - Nur Fitriani; Ridha Anugerah Putra; Indra Basir (Jurnal Proaksi, 2025)
Main Purpose - The objectives of this study are to examine financial literacy and government policies on the sustainability of MSMEs and the role of green financing as a moderator in West Sulawesi. Method – The research method used quantitative explanatory using a structural equation modelling-partial least square (SEM-PLS) approach. Main Findings –  Although green financing has been implemented nationally, at the regional level, such as in West Sulawesi Province, the policy has not been translated into operational guidelines and applicable products for MSME actors. This condition has resulted in low indicators of access and ease of distribution (range restriction), so that direct and moderating effects are not statistically detectable, and the impact of green financing on MSME sustainability has not been empirically identified.Theory and Practical Implications –  The results of the study imply the need to strengthen the financial literacy of MSME actors in sustainable business management. Government policies need to focus on simple procedures and easily accessible incentives, while the implementation of green financing in the regions needs to be accelerated through the development of adaptive products and assistance so that its contribution to the sustainability of MSMEs can be measured. Novelty – The novelty of this research is green finance policies for sustainability of green MSMEs in emerging regions such as Province of West Sulawesi in terms of the relationship between the variables related to this research.